THE CHURCH OF ENGLAND AND THE 1870 ELEMENTARY EDUCATION ACT. Issue 5 (2nd September 2020) - Parker, Stephen G.; Allen, Sophie; Freathy, Rob
ABSTRACT: Set against the background of mid-nineteenth century concerns about an erosion in the denomination's standing and influence, this article highlights the differing responses to the matter from parties within the Church of England, which determined their degree of sympathy with proposals for an education act. Specifically, we point out that the debate over schooling between co-religionists centred upon rival understandings of religious education: 'denominational' and 'undenominational'. We examine the claims of some contemporary High Church leaders and later commentators, that acceding to elements of the 1870 Act, specifically the 'conscience' and 'Cowper-Temple' clauses, represented a pyrrhic victory and that in doing so the Church appeared to resile from its place in society. However, we argue that, though the Church could no longer be described as 'England's educator', it retained considerable influence within the evolving school system and in policymaking. Moreover, we point out that 'denominational' religious education continued to be championed, having diffusive influence, well into the twentieth century. Finally, just as understanding nineteenth-century ecclesiastical history and religious culture is crucial to understanding this moment in the educational past, we argue that a thoroughgoing religious historical literacy is essential to understanding educational policy development regardless of the period under scrutiny.